2020
DOI: 10.2147/ott.s278912
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of a Functional ceRNA Network to Explore Potential Biomarkers for Hepatocellular Carcinoma</p>

Abstract: To establish a novel circRNA-miRNA-mRNA network associated with the poor prognosis of hepatocellular carcinoma (HCC). Materials and Methods: Quantitative real-time PCR was used to verify the differentially expressed circRNA. Moreover, the competing endogenous RNA networks were established using bioinformatics methods. Meanwhile, the prognostic value and potential mechanism of ceRNA network in hepatocellular carcinoma (HCC) were analyzed. Results: This work found that circ_0130911 was highly expressed in HCC ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Emerging evidence indicates that circRNA is abnormally expressed in the development of HCC [ 18 , 19 ]. On the basis of the functions of circRNA in HCC, many circRNAs have been discovered as biomarkers in recent years [ 20 ]. In this study, we identified circRNA hsa_circ_0011385 from the GSE97332 dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that circRNA is abnormally expressed in the development of HCC [ 18 , 19 ]. On the basis of the functions of circRNA in HCC, many circRNAs have been discovered as biomarkers in recent years [ 20 ]. In this study, we identified circRNA hsa_circ_0011385 from the GSE97332 dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Exosome-transmitted circular RNA circ_0051443 suppresses HCC progression by miR-331-3p/BAK1 axis [10]. More recently, some bioinformatic analyses have identified various circRNAs that differentially expressed in HCC tissues and cell lines, and they may participate in tumor progression [11][12][13]. Although circRNAs are considered to have a significant effect on HCC development and progression, the exact mechanisms remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%